Medullary Thyroid Cancer Patient's Assessment of Quality of Life Tools: Results from the QaLM Study. Issue 1 (23rd March 2021) - Moss, Laura; Cox, Catrin; Wadsley, Jonathan; Newbold, Kate; Strachan, Mark W.J.; Druce, Maralyn; Tolley, Neil; Graham, Kathryn; Jefferies, Sarah; Fresco, Lydia; Sivabalasingham, Suganya; Balfour, Alistair; et al.
Abstract : Background: Medullary thyroid cancer (MTC) is a neuroendocrine tumour and a rare variant of thyroid cancer with different aetiology, presentation and treatment to differentiated thyroid cancer. Currently available thyroid cancer-specific quality of life (QoL) tools focus on issues and treatments more relevant to patients with differentiated thyroid cancer and therefore may not address issues specific to a MTC diagnosis and cancer journey. Method: This prospective multicentre randomised study involved 204 MTC patients completing four quality of life questionnaires (QOLQ) and stating their most and least preferred. The questionnaires were a general instrument, the EORTC QLQ-C30, two disease-specific tools, the MD Anderson Symptom Inventory (MDASI) thyroid module and the City of Hope Quality of Life Scale/THYROID (amended) and the neuroendocrine questionnaire, EORTC QLQ-GINET21. Patients were randomised to complete the four questionnaires in one of 24 possible orders and then answered questions about which tool they preferred. The primary outcome measure was patients' preferred QoL instrument for describing their concerns and for facilitating communication with their healthcare professional. Secondary analyses looked at differences between preferred QOLQs amongst patient subgroups (WHO performance status [0 and 1+], disease stage: early [T1–3, N0 or N1A], metastatic [T4, any T N1b] and advanced [any T any N M1], and type of MTC [sporadic and inherited]), identification of MTC patients' least preferred questionnaire and clinicians' views on the QoL tools in terms of their ability to highlight problems not otherwise ascertained by a standard clinical review. Results: No evidence of a difference was observed for most preferred QOLQ ( p = 0.650). There was however evidence of a difference in least preferred questionnaire in the cohort of 128 patients who stated their least preferred questionnaire ( p = 0.042), with 36% (46/128) of patients choosing the EORTC QLQ-GI.NET21 questionnaire. Subgroup analyses showed that there was no evidence of a difference in patients' most preferred questionnaire in sporadic MTC patients ( p = 0.637), patients with WHO PS 0 or 1+ ( p = 0.844 and p = 0.423) nor when comparing patients with early, advanced local or metastatic disease ( p = 0.132, p = 0.463 and p = 0.506, respectively). Similarly, subgroup analyses on patients' least preferred questionnaires showed no evidence of differences in sporadic MTC patients ( p = 0.092), patients with WHO PS 0 or 1+ ( p = 0.423 and p = 0.276), nor in early or metastatic disease patients ( p = 0.682 and p = 0.345, respectively). There was however some evidence to suggest a difference in least preferred questionnaire in patients with advanced local stage disease ( p = 0.059), with 43% (16/37) of these patients choosing the EORTC QLQ-GI.NET21 questionnaire. Conclusions: MTC patients regardless of their performance status, disease aetiology and disease burden did not express a preference for any one particular questionnaire suggesting any of the tools studied could be utilized in this patient cohort. The least preferred questionnaire being a gastrointestinal NET specific tool suggests that diarrhoea was not a significant symptom and concern for the population studied.